P285 Correlation between the endoscopic scoring system SES-CD for Crohn's disease with histological and clinical outcomes. (30th January 2023) - Gibbons, E; Afridi, I; Sheehan, T; Smyth, C; Farrell, R; Hall, B; Kelly, O B
Abstract: Background: There is a growing body of literature demonstrating that persistent histological activity, despite endoscopic remission, may be associated with increased risk of relapse in IBD. Much of this research has focused on outcomes in UC. The primary aim of this study was to examine the correlation of the endoscopic scoring system, SES-CD with histological outcomes and their association with flare/hospitalisation in the ensuing twelve months. Methods: We selected 82 random colonoscopies performed for Crohn's surveillance/assessment between 2017-2019. Adult patients with a complete colonoscopy were included. All reports were reviewed and blindly scored by 2 expert endoscopists using SES-CD scoring system. Histology was classified as normal, mild, moderate and severe by an experienced gastrointestinal histopathologist. Clinical/ IBD demographics, flare episodes and hospitalisations were recorded. Correlation between endoscopic and histologic activity was tested. Comparisons were made between patients with histologic and endoscopic remission, those in endoscopic remission with histologic activity and those with both endoscopic and histologic activity. Results: 82 patients with Crohn's disease (median age 44; M:F 38:44) were included. A wide range of SES-CD scoring was noted (median score 3), with 47.5% in remission (0-2), 30.5% mild activity (3-6), 18% moderate activity (7-15) and 3.5% severe disease activity scoring > 16. Patient groups were similar, p=ns for demographic variables. 29/82 (35%) were in both endoscopic and histologic remission, 10/82 (12%) were in endoscopic remission with persistent histologic activity, and 33/82 (40.2%) had both endoscopic and histologic activity. Histologic activity was independently associated with steroid use/ flare within six months (Z= -2.6, p=0.0075) as was endoscopic activity (Z=-2.76, p=0.0058). Chi analysis of the three groups showed significant differences in the groups, 8.2 p- 0.016 for change in treatment, 9.5 p= 0.008 for steroid use/ flare. 2 way analysis, however, of histologic activity versus deep remission is p=ns, though a trend is apparent. Conclusion: There is now a growing body of evidence that histological remission is an important endpoint. The extent that histologic remission affects outcomes is unclear to date. In a recent 2021 meta-analysis only one study focused on outcomes in Crohn's was included. Further studies are required incorporating greater numbers of patients and robust histologic scoring systems.